Analysis of the Achievement of On-time Performance Perception in Air Transportation Activities - Petra S M Wijaya; Thomas Aquinas Radito; Nerys Lourensius L Tarigan; Hardono Hardono; Febe Agustina Maharani; Syed Waleed Ul Hassan (Universitas Negeri Yogyakarta, 2026)
This study aims to analyze the factors that affect the achievement of on time performance perception in air transportation activities at Yogyakarta International Airport. The factors analyzed include human resources, weather conditions, peak seasons and airline performance. Flight punctuality is one of the main indicators in the assessment of the quality of air transportation services, which has a direct impact on passenger satisfaction. The research method used is a quantitative approach with data collection through questionnaires distributed to airplane passengers at Yogyakarta International Airport. The sample of this study amounted to 100 respondents who were selected using the simple random sampling method. The analysis technique used is multiple linear regression to test the influence of independent variables on dependent variables. The results of the study show that weather conditions, peak seasons and airline performance have a significant effect on the perception of flight punctuality. However, the human resource variable did not have a significant effect, indicating that the professionalism of human resource at the airport did not directly affect passengers' perception of flight punctuality. This finding is expected to be a reference for airports and airlines in improving flight services to better meet passenger expectations.